Prevalence, antimicrobial resistance, and genomic characterization of Salmonella strains isolated in Hangzhou, China: a two-year study - Lifei Yu; Jianzhong Fan; Shanshan Lu; Junxin Zhou; Huangdu Hu; Caiping Mao; Xiaoting Hua; Yan Jiang; Ying Fu; Yunsong Yu; Xinhong Han (BMC, 2024)
Abstract This study explored the molecular epidemiology and resistance mechanisms of 271 non-duplicate Salmonella enterica (S. enterica) strains, isolated mainly from adults (209/271) in a tertiary hospital in Hangzhou between 2020 and 2021. Through whole-genome sequencing and bioinformatics, the bacterial strains were classified into 46 serotypes and 54 sequence types (ST), with S. Enteritidis, S. 1,4,[5],12:i:-, and S. Typhimurium being the most prevalent serotypes and ST11, ST34, and ST19 the most common STs. The strains isolated from adults were primarily S. Enteritidis (59/209), while from children were mainly S. 1,4,[5],12:i:- (20/62). Worryingly, 12.55% strains were multi-drug resistant (MDR), with resistance rates to cefepime (FEP), ceftazidime (CAZ), ceftriaxone (CRO) and cefotaxime (CTX) of 7.38%, 9.23%, 15.87% and 16.24%, respectively, and resistance rates to levofloxacin (LEV) and ciprofloxacin (CIP) of 8.49% and 19.19%, respectively. It is worth noting that the resistance rates of CRO and CTX in children reached 30.65%. A total of 34 strains carried extended-spectrum β-lactamase (ESBL) genes, dominated by bla CTX-M-65 (13/34) and bla CTX-M-55 (12/34); it is notable that one strain of S. Saintpaul carried both bla CTX-M-27 and bla CTX-M-55. The resistance mechanism to cephalosporins was mainly due to ESBL genes (20/43), and other genes included AmpC and β-lactamase genes. The strains resistant to quinolones mainly carried qnrS1 (27/53), and others included qnrB6, aac(6')-Ib-cr, and mutations in gyrA and parC. One strain did not carry common quinolone resistance genes but had a parC (p.T57S) mutation to cause CIP resistance. This research provides vital insights into the molecular epidemiology and resistance mechanisms of clinical S. enterica, implicating possible infection control strategies.